Pretreatment with melatonin improves ovarian tissue cryopreservation for transplantation - Marcos Eiji Shiroma; Luciana Lamarão Damous; Fernanda Pereira Cotrim; Cristiane Lima Roa; José Cipolla-Neto; Russel Joseph Reiter; Edmund Chada Baracat; José Maria Soares (Reproductive Biology and Endocrinology, 2021)
Abstract Backgroud Melatonin has anti-inflammatory and antioxidative actions at the mitochondrial level. This indole-containing molecule may protect ovarian grafts during the process of cryopreservation. Therefore, we aimed to determine whether melatonin pretreatment improves rat ovarian graft quality. Methods Twenty-six female rats were allocated to two study groups of thirteen animals each: 1) control group: ovaries cryopreserved using the standard protocol; and 2) melatonin group: ovaries cryopreserved in a medium with melatonin. Ten rats of each group were submitted to 24-h freezing, and whole ovaries autologous and avascular transplantation with retroperitoneal placement. After postoperative (PO) day 15, daily vaginal smears were obtained for estrous cycle characterization. Between PO days 30 and 35, the animals were euthanized and ovarian grafts were recovered for histological and immunohistochemical (Ki-67, cleaved caspase-3, TUNEL, von Willebrand factor, estrogen, and progesterone receptors) analyses. The ovaries of the three remaining rats from each group were studied immediately after thawing to assess the effects of cryopreservation. ANOVA and Tukey’s tests were used and the rejection level of the null hypothesis was set at 0.05 or 5% (p < 0.05). Results Melatonin promoted faster restart of the estrous cycle and increased the expression of mature follicles, collagen type I, von Willebrand factor, Ki-67, and cleaved caspase-3 on corpora lutea and estrogen receptors in the ovaries as compared to control. There was a reduction in apoptosis by TUNEL on follicles, corpora lutea, and collagen type III. Conclusion Based on the evaluated parameters, melatonin may promote the quality of ovarian grafts. Reproductive function enhancement should be further studied.